An Introduction to the Intellectual Biography of ʿAbd al-Shakūr from the Banten Sultanate - Firmansyah, Agung (Universitas Islam Internasional Indonesia, 2024)
ʿAbd al-Shakūr b. ʿAbd al-Karīm al-Bantanī was a prominent disciple of the renowned scholar Burhān al-Dīn Ibrāhīm b. Ḥasan al-Kūrānī. Despite his importance as a scholar and Sufi shaykh connected to the Shāṭṭārīyah order, ʿAbd al-Shakūr has received relatively little attention compared to other Jāwī students of al-Kūrānī. The research draws on a range of primary sources, including manuscripts copied by ʿAbd al-Shakūr himself or containing references to him, as well as secondary literature. Key findings include the establishment of ʿAbd al-Shakūr’s genealogical ties to the Banten royal family, his role as a scribe and disseminator of his teacher al-Kūrānī’s works, and his participation in the theological discourse of his time, particularly on the concept of waḥdat al-wujūd (the unity of existence). Additionally, the study explores ʿAbd al-Shakūr’s contribution to the spread of the Shāṭṭārīyah Sufi order in the Malay-Indonesian Archipelago, tracing its transmission from al-Kūrānī through ʿAbd al-Shakūr to his son ʿAbd al-Muḥyī al-Dīn and other disciples. The discovery of manuscripts documenting the Shāṭṭārīyah lineage in Jasinga, Bogor, and Mindanao in the Philippines, further highlights ʿAbd al-Shakūr’s significance as a pivotal figure in the dissemination of this Sufi tradition within the region.